Breeding biology of Adélie penguin (Pygoscelis adeliae) at Edmonson Point CEMP site (Ross Sea, Antarctica): report of the first five years - OLMASTRONI, SILVIA; CORSOLINI, SIMONETTA; Pezzo F.; Focardi S.; Kerry K. (Commission for the Conservation of Antarctic Marine Living Resources, 1999)
During 1998/99 austral summer the Adélie penguin monitoring program was carried out for the fifth year. The study site was located in the Adélie penguin (Pygoscelis adeliae) colony of Edmonson Point (74°20'56.7" S, 165°08'10.03" E). The aim of this research was to obtain data to contribute to the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) Ecosystem Monitoring Program and data on the feeding ecology of the Adélie penguin. The rationale for the program is the possibility that the harvest of krill may impact on the reproductive success of its major predators, in this instance the Adélie penguin. It is believed that any such impact will be difficult to detect initially because this species is long lived and changes which may affect the long term survival will be subtle. Large sample sizes and long monitoring research will be required to detect change. The penguin rookery was studied in terms of colony layout, breeding chronology, foraging trip duration, feeding localities and diet composition of breeding male and female. Penguins were monitored using satellite transmitters, time-depth recorders, and electronic tagging . An Automated Penguin Monitoring System (APMS) was installed which records the weight, identity and direction of penguins as they move between the sea and their breeding colony and support these data with direct observations. The penguins at Edmonson Point are guided by small fences to cross the weigh bridge. This enables researchers to monitor all birds which enter the study area of 500-600 nests. The results of this study up today allowed documentation on colony trends and on breeding biology and showed gender differences in foraging strategies among different stages of reproductive period and among different study seasons. Moreover the automated system enabled collection of baseline data on Edmonson Point penguins population reducing researchers disturbance to the colony.